Late Quaternary sea-level change, sedimentation and neotectonics of the Gulf of Gokova:: Southeastern Aegean Sea - Ulug, A; Duman, M; Ersoy, S; Özel, E; Avci, M (ELSEVIER SCIENCE BV, 2005)
The sedimentary and tectonic Late Quaternary evolution of the Gulf of Gokova located at the southwest Anatolia-southeastern Aegean Sea region has been interpreted from 800 line km of 3.5 kHz and single channel airgun seismic reflection profiles. The older part of the Gokova basin is formed by mainly E-W trending faults and filled by the latest Miocene-Pliocene-Quaternary hemipelagic sediments with thickness up to 2.5 km. The Lycian Nappes, which primarily cover extreme southwestern Anatolia, represent the basement rocks for the Gokova region. Younger active faulting so-called Gokova Transfer Fault (GTF), which has not been previously discussed in the literature, trends NE in the central part of the Gulf of Gokova basin and records sinistral strike-slip motion broadly parallel to the convergence direction of the Aegean-Anatolian and African plates. The continental shelf of the northeastern Gulf of Gokova is mostly formed by numerous superimposed deltaic successions (depositional sequences), separated by major erosional unconformities. During times of lowered sea-level associated with late Quaternary glaciations, deltas prograded more than 40 km seaward from their present positions. Foreset progradation terminated with the rise of sea level in interglacial and post-glacial times and deltas were relocated far inland. These major transgressions resulted in unconformities that are correlated with the beginning of oxygen isotope stages 9, 7, 5 and 1, and provide chronostratigraphic markers for a detailed analysis of sedimentation patterns in the late Quaternary. All seismic lines show that the topset to foreset transition of the youngest Pleistocene delta system developed around 145-150 ms below present sea-level. Thus, the maximum Pleistocene sea-level lowering (18 000 years BP) was about -110 m. The positions of maximum regression for isotopic stages 6, 8 and 10 were found as 160, 190 and 215 in below present sea-level, respectively. Paleo shoreline positions during isotopic stages 2, 6 and 8 suggest an overall gradual subsidence of Gokova basin, during the last 0.5 Ma in the southeastern Aegean Sea. The seismic sedimentary chronology suggests that the Gokova Basin is subsiding at 0.3-0.4 mm/year. Three bathymetric low and E-W, WNW-ESE directed two main ridges in the gulf area are noticeable from the bathymetric data and are well correlated to the seismic data. While the main orientation of the gulf is E-W, more recent ENE-WSW and WNW-ESE structures are remarkable in the western and the mid-eastern part of the gulf respectively. Subsidence rates are greatest in the southern center of the basin and decrease northward, so that the northern area is being tilted southward. (c) 2005 Elsevier B.V All rights reserved.
Keywords: Aegean Sea; seismic stratigraphy; sea-level changes; Late Pleistocene; delta; tectonics; WESTERN TURKEY; SOUTHWEST ANATOLIA; ACTIVE TECTONICS; LATE MIOCENE; EVOLUTION; GREECE; HISTORY; REGION; ARC; PLEISTOCENE; Geology; Oceanography